2020
DOI: 10.21043/iqtishadia.v13i2.7809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Digitalization Zakat Payment Against Potential of Zakat Acceptance in National Amil Zakat Agency

Abstract: <p>The purpose of this study was to determine the effect of digitalization zakat payments on the potential for zakat acceptance at the BAZNAS Jakarta center. The originality of this research lies in the digitalization analysis of zakat payments to increase the potential for receiving BAZNAS center based on sharia economic approaches, and digital technology theory. The research method used is associative quantitative using a simple linear regression analysis technique with a sample size of 170 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
4
26
0
5
Order By: Relevance
“…In this study, the results of the convenience variable are similar to the findings of Ichwan (2020), Sukoraharjo (2018), and Karmanto & Baskoro (2020) that the convenience variable affects the interest in paying zakat. One of the challenges faced with digital zakat payments is that internet access in Indonesia is still uneven (Utami et al, 2020). Rachmat et al (2020) stated that there are several other factors that determine the behavior of Gen Y Muslims in the use of digital zakat payments.…”
Section: Table 1 Number Of Respondents Based On Payment Methodsmentioning
confidence: 99%
“…In this study, the results of the convenience variable are similar to the findings of Ichwan (2020), Sukoraharjo (2018), and Karmanto & Baskoro (2020) that the convenience variable affects the interest in paying zakat. One of the challenges faced with digital zakat payments is that internet access in Indonesia is still uneven (Utami et al, 2020). Rachmat et al (2020) stated that there are several other factors that determine the behavior of Gen Y Muslims in the use of digital zakat payments.…”
Section: Table 1 Number Of Respondents Based On Payment Methodsmentioning
confidence: 99%
“…This further reinforces that in the next few years, community activities for online transactions will become a trend in Indonesia, including zakat. Therefore, this study intends to examine how people's behavior in using technology to pay zakat online.A study conducted by Utami, Suryanto, Nasor, & Ghofur (2020) proves that digitalization has an effect on the potential for collecting zakat funds. This indicates that the digitalization strategy for collecting zakat will increase the amount of zakat collection by OPZ.…”
Section: Figure1 Digitalization Of Zakat Management In Indonesiamentioning
confidence: 99%
“…However, the use of digital technology entails challenges in its implementation, as reported by several researchers. Utami et al (2020) reported that the challenges in implementation of zakat digitalisation in Indonesia lie in the unequal distribution of reliable internet access in Indonesia, the importance of building a "bond" among mustahiq, muzzaki and BAZNAS, as well as the application of Sharia in the management of zakat. Regarding regulatory aspects, Ulya (2018) found that the existing regulations only regulate the application of fintech in profit organizations, while there is no specific regulation or legal protection for donation-based crowdfunding (zakat) on fintech, which is a type of non-profit product for religious and social purposes.…”
Section: Performance Of Zakat Management Organisationsmentioning
confidence: 99%